2016
DOI: 10.1038/srep20831
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide—Mechanisms of Toxicity and Development of an Antidote

Abstract: Hydrogen sulfide is a highly toxic gas—second only to carbon monoxide as a cause of inhalational deaths. Its mechanism of toxicity is only partially known, and no specific therapy exists for sulfide poisoning. We show in several cell types, including human inducible pluripotent stem cell (hiPSC)-derived neurons, that sulfide inhibited complex IV of the mitochondrial respiratory chain and induced apoptosis. Sulfide increased hydroxyl radical production in isolated mouse heart mitochondria and F2-isoprostanes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(185 citation statements)
references
References 48 publications
(79 reference statements)
2
183
0
Order By: Relevance
“…10, 30, 32 Here, we examined the skeletal effects of a novel NO donor, nitrosyl-cobinamide (NO-Cbi), derived from the vitamin B 12 precursor cobinamide; it releases NO directly, without biotransformation or generation of reactive oxygen species. 3336 We found that NO-Cbi enhanced trabecular bone mass in intact and OVX mice by enhancing osteoblast activity and inhibiting osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…10, 30, 32 Here, we examined the skeletal effects of a novel NO donor, nitrosyl-cobinamide (NO-Cbi), derived from the vitamin B 12 precursor cobinamide; it releases NO directly, without biotransformation or generation of reactive oxygen species. 3336 We found that NO-Cbi enhanced trabecular bone mass in intact and OVX mice by enhancing osteoblast activity and inhibiting osteoclast differentiation.…”
Section: Introductionmentioning
confidence: 83%
“…Boss et al, unpublished data and 33 ). After NO release, cobinamide is generated, and cobinamide can bind O 2 − and other reactive oxygen species, 36 providing a potential added benefit of protecting cells from oxidative stress. Repeated administration of NO-Cbi does not induce tolerance, and NO-Cbi is stable and can be administered by multiple routes, including oral ingestion (G.R.…”
Section: Discussionmentioning
confidence: 99%
“…Only one in three surviving rats that received a higher dose demonstrated frank lesions 1 week after exposure . In an inhalation mouse model using anesthetized mice, the focus of the study was biochemical changes, and neurodegeneration was not evaluated . None of these alternative models examined sex differences in rats or mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since the details of these interactions in physiological circumstances are still emerging, any associated pathological biochemistry is even less well delineated, but there is promising scope here for the discovery of a mechanism to explain H 2 S-induced pulmonary edema and, thus, potential therapeutic targets. There has been some recent focus on the lung epithelial sodium channel as a target for treating H 2 S-induced acute pulmonary edema [178180]. Unfortunately, there is cause for pessimism with regard to this suggestion because multicenter clinical trials with epithelial sodium channel activators/stimulators for the treatment of patients with pulmonary edema have, thus far, proven disappointing [181].…”
Section: Conflicting Observations Regarding the Chemical Toxicologmentioning
confidence: 99%